Long Simple Sequence Repeats in Host-Adapted Pathogens Localize Near Genes Encoding Antigens, Housekeeping Genes, and Pseudogenes - Guo, Xiangxue; Mrázek, Jan (Journal of molecular evolution, 2008)
Simple sequence repeats (SSRs) in DNA sequences are tandem iterations of a single nucleotide or a short oligonucleotide. SSRs are subject to slipped-strand mutations and a common source of phase variation in bacteria and antigenic variation in pathogens. Significantly long SSRs are generally rare in prokaryotic genomes, and long SSRs composed of iterations of mono-, di-, tri-, and tetranucleotides are mostly restricted to host-adapted pathogens. We present new results concerning associations between long SSRs and genes related to different cellular functions in genomes of host-adapted pathogens. We found that in the majority of the analyzed genomes, at least some of the genes associated with SSRs encode potential antigens, which is expected if the primary function of SSRs is their contribution to antigenic variation. However, we also found a number of long SSRs associated with housekeeping genes, including rRNA and tRNA genes, genes encoding ribosomal proteins, amino acyl-tRNA synthetases, chaperones, and important metabolic enzymes. Many of these genes are probably essential and it is unlikely that they are phase-variable. Few statistically significant associations between SSRs and gene functional classifications were detected, suggesting that most long SSRs are not related to a particular cellular function or process. Long SSRs in Mycobacterium leprae are mostly associated with pseudogenes and may be contributing to gene loss following the adaptation to an obligate pathogenic lifestyle. We speculate that LSSRs may have played a similar role in genome reduction of other host-adapted pathogens.